(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article investigates ecological consciousness as a key factor in achieving sustainable development, emphasizing its philosophical and psychological foundations. It analyzes how awareness and attitudes toward environmental issues are shaped by cognitive, cultural, and moral dimensions of human behavior. Drawing on interdisciplinary perspectives, the study explores the interplay between personal responsibility, collective ecological thinking, and global sustainability. Particular attention is given to the context of Uzbekistan, where environmental challenges require a deeper internalization of eco-values. The article advocates for educational and social strategies that cultivate ecological mindfulness as a necessary condition for fostering long-term ecological balance and ethical environmental governance.